(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2025)
The 21st century has brought a paradigm shift in education, particularly in primary education, where digital tools and modern teaching methods are being increasingly integrated. This study explores how the combination of modern pedagogical methods and educational technologies contributes to improving the effectiveness of teaching and learning processes in primary schools. Through classroom observation, teacher interviews, and pupil feedback, the research identifies benefits, challenges, and outcomes of this integration. The findings reveal that a well-balanced use of digital tools and innovative methods enhances engagement, motivation, and cognitive development among young learners.